DUALITAS MAKNA SHADHDHAH DALAM NOMENKLATUR QIRA‘AT: Sejarah dan Perkembangannya dalam Qira‘at Shadhdhah - Miftahul Jannah (UIN Siber Syekh Nurjati Cirebon, 2018)
This paper examines the history of qiraat, especially qiraat syÄzzah. Qiraat syÄzzah allegedly arose during the Caliph of UsmÄn along with the presence of muá¹£á¸¥af 'usmÄnÄ«. However, when there is no syÄzzah term itself. Newly in the time of Ibn Mujahid, the term syÄzzah is well established in the qiraat discipline as opposed to qira'at sab'ah. From this, questions arise, what is the term used before the time of Ibn Mujahid? How does or how to identify qiraat syÄzzah? How do the scholars respond to the term syÄzzah popularized by Ibn Mujahid? Therefore, this study is significant not only to see the wealth of the opinion of the Ulama, but to indicate the existence of the continue and change in the area of qiraat syÄzzah thinking. The diversity of opinions conveys the shift in the use of the term syÄzzah of quantity into quality, which originates from the least reading being da'if.